INTERNALIZATION OF EXAMPLE VALUES IN SOCIAL SCIENCE LEARNING - Agus Salam (International Journal of Teaching and Learning, 2024)
Exemplification in education is an effective method that most ensures success in preparing and forming students with noble character and morals. Social studies subjects are one of the fields of science taught in junior high schools. In relation to the internalization of exemplary values, this research will focus on Social Sciences subjects in an integrated manner. To teach exemplary values in social studies learning, of course it cannot be taught using a factual teaching approach (lecture), but appropriate approaches must be used so that students understand, appreciate and integrate the values of national character which will be integrated into competency standards and basic competencies in social studies subjects. In this case, social studies as a school subject not only develops theoretical values that prioritize logic and rationality, but also becomes a subject that can be used to develop other values. By providing conducive Social Sciences (IPS) learning conditions, it will enable students to be directly involved in learning as an effort to develop knowledge, values, attitudes, morals and social skills.